An Epidemiological Study of Sharp Injuries among Health Care Workers of Tertiary Care Hospital in Saudi Arabia - Sanjay Kumar Gupta; Mohammad Jawaid Arif; Sinimol Jabar; Sunitha Lorin Mathias; Ibrahim Saifi Al Harbi (Medsci Publications, 2019)
Introduction: Needle stick injury: A penetrating stab wound from a needle (or other sharp object) that may result in exposure to blood or other body fluids to the health care workers (HCW). The study was conducted to know the pattern of needle stick injuries among health care workers and epidemiological link. Methodology: This was a hospital based retrospective study conducted in a tertiary care hospital. Observations: Total 93 incident of sharp injury were reported, of which majority were among nurses (55%) and maximum occurred in operation theatre (29%). 61% health care workers got injury by needle sticks 57 (61%) followed by during surgical procedures (38%). Most common duration of sharp injuries was morning sift 67 (72%) and difference between morning sift and evening sift was statistically significant (X2 = 47.7, p=0.000). The common site of hand in left hand among health care workers was index finger and thumb respectably 15 (16%) and 21 (23%). Conclusion: Present study shown that majority of injuries occurred in morning sift and moderate in nature common among nursing staffs happened during administration of injection and blood extraction in left hand thumb and index finger.